Dreamland's: know about science inventions 2 - Talwar, L.M (Dreamland Publications New Delhi, 1995)
Dreamland's: Know About Science - Inventions explores the world of inventions and how they have shaped our lives. It highlights notable inventions throughout history, explaining their significance and the creative processes behind them. Through vivid illustrations and relatable examples, the book inspires curiosity about innovation and encourages children to think about their own ideas for future inventions.